2021
DOI: 10.1186/s41983-021-00325-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis outcome in posterior vs anterior circulation stroke in a tertiary stroke center in Egypt

Abstract: Background Intravenous thrombolysis (IVT) with alteplase is the first-line therapy for acute ischemic anterior and posterior circulation strokes (ACS and PCS). Knowledge about safety and efficacy of IVT in posterior circulation stroke is deficient as most of the Egyptian studies either assessed IVT outcome in comparison to conservative therapy or its outcome in anterior circulation stroke only. Therefore, our aim was to compare the relative frequency and outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…In line with some previous observations, our PCS patients were younger and more often males [6,8,27,38], had less severe baseline NIHSS scores [7,8,10,[12][13][14]38,39], lower occurrence of atrial fibrillation [6,[8][9][10]15,27,38,39], higher blood glucose levels [6,8,15] and slower ONT and DNT [8,13] in comparison to ACS patients. The reported occurrence of other conventional stroke risk factors, clinical parameters, and prophylactic treatment recorded at admission or discharge in both groups has varied widely across studies with diverse degrees of statistical significance.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with some previous observations, our PCS patients were younger and more often males [6,8,27,38], had less severe baseline NIHSS scores [7,8,10,[12][13][14]38,39], lower occurrence of atrial fibrillation [6,[8][9][10]15,27,38,39], higher blood glucose levels [6,8,15] and slower ONT and DNT [8,13] in comparison to ACS patients. The reported occurrence of other conventional stroke risk factors, clinical parameters, and prophylactic treatment recorded at admission or discharge in both groups has varied widely across studies with diverse degrees of statistical significance.…”
Section: Discussionsupporting
confidence: 91%
“…Historically, patients with PCS have been thought to have a poorer outcome with high morbidity and mortality [47,48], but latter studies have shown the opposite to be true. Most of the studies have found that the 3-month outcomes after IVT treatment alone in patients with PCS were better or very much alike to ACS patients, including the significantly more frequent achievement of both excellent (55.7 vs. 41.6% [15] and 45.2 vs. 37.5% [8]) and good (63.9 vs. 53.0% [15], 61.3 vs. 49.4% [8] and 93.8 vs. 70.2% [14], respectively) outcomes. These results run parallel with our findings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation